The Plasmodium palmitoyl-S-acyl-transferase DHHC2 is essential for ookinete morphogenesis and malaria transmission - Santos, Jorge M.; Kehrer, Jessica; Franke-Fayard, Blandine; Frischknecht, Friedrich; Janse, Chris J.; Mair, Gunnar R. (Scientific reports, 2015)
The post-translational addition of C-16 long chain fatty acids to protein cysteine residues is catalysed by palmitoyl-S-acyl-transferases (PAT) and affects the affinity of a modified protein for membranes and therefore its subcellular localisation. In apicomplexan parasites this reversible protein modification regulates numerous biological processes and specifically affects cell motility and invasion of host cells by Plasmodium falciparum merozoites and Toxoplasma gondii tachyzoites. Using inhibitor studies we show here that palmitoylation is key to transformation of zygotes into ookinetes during initial mosquito infection with P. berghei. We identify DHHC2 as a unique PAT mediating ookinete formation and morphogenesis. Essential for life cycle progression in asexual blood stage parasites and thus refractory to gene deletion analyses, we used promoter swap (ps) methodology to maintain dhhc2 expression in asexual blood stages but down regulate expression in sexual stage parasites and during post-fertilization development of the zygote. The ps mutant showed normal gamete formation, fertilisation and DNA replication to tetraploid cells, but was characterised by a complete block in post-fertilisation development and ookinete formation. Our report highlights the crucial nature of the DHHC2 palmitoyl-S-acyltransferase for transmission of the malaria parasite to the mosquito vector through its essential role for ookinete morphogenesis.
Gesehen am 15.06.2020